THE EFFECT OF LIPOCALIN-2 IN PERIODONTAL DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Current evidence suggests that Lipocalin-2 is a protein secreted from bone tissue and is elevated in the presence of periodontal disease. This systematic review will allow us to assess the concentration of LCN-2 in patients with periodontal disease, identify the most appropriate biological fluids for its detection, identify the form of periodontal disease in which this protein is most highly expressed, as well as to study the relationship of LCN-2 with other inflammatory markers and systemic diseases, and to monitor changes in its expression during treatment.